Psychotropic Drugs and Transdermal Delivery: An Overview - GEETA AGGARWAL; SANJU DHAWAN (International Journal of Pharma and Bio Sciences, 2010)
Optimum therapeutic outcomes require not only proper drug selection, but also effective drug delivery. Scientists are exploring new methods of drug administration to improve patient compliance and enhance drug response. In many instances, oral administration of psychotropics is considered a less than optimal medication delivery system due to non-compliance. One potential method to help promote compliance is to develop psychotropic medications that can be delivered via a transdermal patch. Transdermal patches are used for treatment of various indications including pain, pregnancy prevention, and hormone replacement. In many cases, transdermal medication delivery is believed to offer many advantages over conventional oral therapies. Transdermal patches may help to improve tolerability by providing smoother continuous drug delivery. Selegiline, fluoxetine, haloperidol, imipramine, methylphenidate and rivastigmine transdermal systems have already been developed and may provide a promising new approach for other psychotropic drugs. Recent improvements in transdermal drug delivery through the use of permeation enhancers, transdermal gels, iontophoresis, electroporation and sonophoresis appear to be promising technologies for future psychotropics utilizing transdermal medication delivery.